Taxonomic review of the genus Pygophora Schiner of Japan (Diptera: Muscidae) - Yoshizawa, Satoshi; Tachi, Takuji (Zootaxa, 2018)
Japanese species of the genus Pygophora Schiner, 1868 are reviewed, with redescription of the following species: P. boninensis Snyder, 1965; P. confusa, 1915; P. immaculipennis Frey, 1917; P. lepidofera (Stein, 1915); P. longicornis (Stein, 1918); P. macularis (Wiedemann, 1830); P. maculipennis Stein, 1909; P. respondens (Walker, 1859); P. unicolor (Stein, 1920). New occurrence records are presented to P. macularis (Wiedemann, 1830), P. respondens (Walker, 1859), and P. unicolor (Stein, 1920). Pygophora trimaculata Karl, 1935 is excluded from Japanese species, as it had been based on a misidentification. The male and female terminalia are illustrated, and an identification key to the Japanese species is provided.